Литературная деятельность Виктора Ерофеева „военного” периода - Panaotović, Melina (Studia Rossica Posnaniensia, 2026)
With the beginning of Russia’s invasion of Ukraine, more precisely since February 2022, the Russian-speaking world has changed. Europe has witnessed a kind of cancellation of Russian culture; art has been divided into “ours” and “not ours”. Some authors have left Russia, while others have stayed. In this article, we will discuss the literary activity of Viktor Yerofeyev in this new wartime context. In the work of this pioneer of Russian postmodernism we can observe strong journalistic tendencies. Yerofeyev actively collaborates with European magazines (mainly in Germany, France, and Serbia) and writes about contemporary life in Russia (e.g. in the articles Time of denunciations and Insane Russia), his understanding of the war (The metaphysical impasse of the Russo-Ukrainian war; The end of the war is just around the corner; Putin’s perestroika sweeps everything away), as well as about his life abroad (articles Kafka’s absurdity in Deutsche Bank and Escape from the mortuary). In addition to his journalistic work, Yerofeyev continues his literary career as a compiler and one of the authors of the almanac Coming out. In this paper, we will focus on this almanac, considering it a genuine testimony to the active state of Russian literature today.